Number 6 (February 1978) - W. C. Starnes; L. B. Barnes (Southeastern Fishes Council Proceedings, 1978)
Status Report on a New and Threatened Species of Phoxinus from the Upper Cumberland Drainage. By W.C. Starnes and L.B. Starnes, plus News Notes, 4 pp.
Keywords: fishes; Phoxinus; Upper Cumberland Drainage